Measuring the Effectiveness of Zakat Distribution at the National Board of Zakat of Bandung City - Bahri, Efri Syamsul; Aslam, Mohd Mizan Mohammad; Wibowo, Hendro; Mubarok, Abdullah (ITQAN: Journal of Islamic Economics, Management, and Finance, 2023)
Zakat, collected by the National Board of Zakat (Baznas) of Bandung City, has practical value for the community's welfare. This study aims to measure the effectiveness of Zakat distribution in Baznas Bandung City. This research was conducted using quantitative methods. Data sourced from the Baznas Bandung City Financial Report for the 2017-2021 period. Distribution effectiveness measurement uses the allocation-to-collection ratio (ACR) approach. In addition, this study uses a descriptive approach. The results showed that the ACR value was 94 per cent. Thus, the level of effectiveness in the distribution of Baznas Bandung City is in the Highly Effective category. Therefore, Baznas Bandung City needs to optimize the distribution of Mustahiq Zakat, which covers five program areas: Education, Economy, Health, Da'wah, and Humanity.